2020
DOI: 10.3390/plants9080980
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Uptake by Two Tolerant Grass Species: Holcus lanatus and Agrostis capillaris Growing in Soils Contaminated by Historical Mining

Abstract: The study focused on two grass species Holcus lanatus and Agrostis capillaris abundant in the sites of former As mining and processing in the Sudetes. Arsenic uptake from soils was examined to assess a risk associated with its accumulation in grass shoots and to check its dependence on soil fertilization. The research involved a field study and greenhouse experiment. In the field study, soil and plant samples were collected from 33 sites with 72–98,400 mg/kg total soil As. Arsenic uptake by grasses differed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Field results confirmed previous screening studies 4 , 14 , showing significant differences in arsenic concentrations in the aboveground biomass of A. capillaris in arsenic-enriched areas. The screening allowed to indentify single individuals of bentgrass with As concentrations in shoots over 110 mg kg −1 , and those in roots up to 9400 mg kg −1 4 , 14 , which would possibly qualify this species as an As hyperaccumulator. Some authors have reported that A. capillaris can hyperaccumulate metal(loid) elements, including Pb and As, though this is controversial and questioned by others 18 , 67 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Field results confirmed previous screening studies 4 , 14 , showing significant differences in arsenic concentrations in the aboveground biomass of A. capillaris in arsenic-enriched areas. The screening allowed to indentify single individuals of bentgrass with As concentrations in shoots over 110 mg kg −1 , and those in roots up to 9400 mg kg −1 4 , 14 , which would possibly qualify this species as an As hyperaccumulator. Some authors have reported that A. capillaris can hyperaccumulate metal(loid) elements, including Pb and As, though this is controversial and questioned by others 18 , 67 .…”
Section: Discussionsupporting
confidence: 88%
“…Chemical analysis of A. capillaris collected from all four field sites S1-S4 confirmed that generally the plants poorly took up arsenic, clearly demonstrating an avoidance strategy. The concentrations of As in plant roots were much higher than those in the aboveground parts of plants, which is typical for this element 3 , 25 , 26 , and was already reported in previous screening studies from the area of Złoty Stok 4 , 14 . The values of the root-to-shoot translocation coefficients (TF) were consequently very low, in particular in the most strongly contaminated sites S1, S2 and S4, where they did not exceed 0.06 (Table 3 ).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A rapid reduction of AsO 4 3− to AsO 3 3− catalyzed by AR often is followed by complexation with thiols and possibly sequestration into the root vacuoles, which results in lower mobility and translocation of As from the roots to the shoot, except in hyperaccumulators (Zhao et al, 2009). Possibly, due to these As detoxification processes, other grass species, such as Agrostis capillaris, Holcus lanatus (Dradach et al, 2020b), Festuca rubra (Dradach et al, 2020a), and Pennisetum purpureum (also known as Cenchrus purpureus) (Kowitwiwat and Sampanpanish, 2020), have higher As concentrations in the roots than in the shoots. Symptoms of As-induced toxicity are closely related to changes in the integrity of plasma membranes that affect nutrient uptake and plant water status.…”
Section: Arsenicmentioning
confidence: 99%
“…Changing conditions of soil pH or redox potential can considerably affect As sorption and cause its release from (hydro)oxides. Introduction of phosphates or organic matter into the soil may also contribute to the desorption of As from the soil solid phase (Wenzel, 2013;Berg, 2017;Cuske et al, 2017;Dradrach et al, 2020aDradrach et al, , 2020b. All these factors make As bioavailability strongly dependent on soil properties (Song et al, 2006;Wenzel, 2013).…”
Section: Introductionmentioning
confidence: 99%